PENENTUAN KEBIJAKAN PERSEDIAAN SPARE PART JOK MOBIL DENGAN PENDEKATAN METODE ABC, ECONOMIC ORDER QUANTITY (EOQ), PERIOD ORDER QUANTITY (POQ) UNTUK MENURUNKAN BIAYA PERSEDIAAN PT. XYZ - Bintang Naufal Fauzan; Asep Hermawan; Rizky Fajar Ramdhani (LPPM Sekolah Tinggi Teknologi Nusantara Lampung, 2024)
PT. XYZ is a manufacturing company in the automotive industry that produces car seats. This thesis explains how to determine the amount of spare part inventory that is more economical and efficient. The technique for determining inventory in this research is determining the most economical price (Economic Order Quantity), safety stock, reordering (Reorder Point), and the number of orders per period (Period Order Quantity). Based on the results of research using the EOQ method, the number of spare part purchases was 112,149 pieces, the economic inventory cost (EOQ) was IDR 3,350,290 for reorders per period (ROP), with a quantity of 139,595 pieces. The quantity per period (POQ) is around 99 orders with a total quantity of 532,372.40 pieces, for inventory costs according to the period (POQ) is IDR 3,195,422. Conclusions and this research shows that the order quantity is more economical compared to the method used by PT XYZ.